2023
DOI: 10.1101/2023.10.11.561987
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resolving the pharmacological redox-sensitivity of SARS-CoV-2 PLpro in drug repurposing screening enabled identification of the competitive GRL-0617 binding site inhibitor CPI-169

Maria Kuzikov,
Stefano Morasso,
Jeanette Reinshagen
et al.

Abstract: The SARS CoV-2 Papain-Like protease has multiple roles in the viral replication cycle, related to both its polypeptide cleavage function and its capacity to antagonize host immune response. Targeting PLpro function is recognized as a promising mechanism to modulate viral replication whilst supporting host immune responses. However, development of PLpro specific inhibitors remains challenging. Upcoming studies revealed the limitation of reported inhibitors by profiling them through a pipeline of enzymatic, bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…PLpro cleaves ubiquitin, interferon-stimulated gene 15 (ISG15) or neural precursor cell-expressed developmentally downregulated protein 8 (NEDD8) from substrates thus impairing the host’s functions [ 45 ]. Recent studies have shown that the three PLpros have different substrate specificities that can be exploited for the design of selective inhibitors to limit the diverse viral infections [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…PLpro cleaves ubiquitin, interferon-stimulated gene 15 (ISG15) or neural precursor cell-expressed developmentally downregulated protein 8 (NEDD8) from substrates thus impairing the host’s functions [ 45 ]. Recent studies have shown that the three PLpros have different substrate specificities that can be exploited for the design of selective inhibitors to limit the diverse viral infections [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%